Catch assessment of artisanal marine fishing gears in Coxs Bazar and Teknaf of Bangladesh (Progressive Agriculture, 2016)
Studies were conducted on catch assessment of some artisanal marine fishing gears operated in Coxs Bazar and Teknaf areas from April 2014 to April 2015. Sixteen types of fishing gears were identified, of which gill net, beach seine net, estuarine set bag net, marine set bag net and trammel net occupy major fishing activities. Although estuarine set bag net (ESBN) is a legally restricted fishing gear recorded the highest catch per unit effort (CPUE) (110 kg/gear/day) in July followed by marine set bag net (MSBN) (105 kg/gear/day) in Coxs Bazar and the highest CPUE was recorded 100 kg/gear/day by ESBN in June followed by MSBN (90 kg/gear/day) in Teknaf. Out of 52 species of fishes, the major fish species abundantly caught by these gears were Poa (Otolithoides argenteus), Churi (Trichiurus haumela), Loittya (Harpadon nehereus), Ranga choukha (Lutjanus johni), Lal poa (Johnius argentatus), Olua (Coilia dussumieri), Rup chanda (Stromateus chinensis), (Stromateus argenteus) and Ilish (Tenualosa ilisha). Besides these fish species, 10 commercially important shrimp species and 3 important crab species were also recorded during the study period. The peak season of availability of most fish species was June and July while lean season was December and January. This study indicated that Otolithoides argenteus) was the dominant fish species followed by Trichiurus haumela, Harpadon nehereus and Coilia dussumieri.Progressive Agriculture 27 (2): 228-234, 2016